Effect of heat processing on bioactive compounds of dehydrated (lyophilized) purple mashua (Tropaeolum tuberosum) (Scientia Agropecuaria, 2023)
Mashua (Tropaeolum tuberosum) is an Andean tuber rich in phenolic compounds and glucosinolates, known for its consumption that allows the prevention and/or reduction of getting diseases. The present research evaluated the effect of different types of post-harvest management (sunny, bleached, and freeze-dried) on glucosinolate content and its relationship with myrosinase activity. It is also important to note that when plant cells are damaged and glucosinolates meet the plant's myrosinase, which hydrolyzes them and degrades them to other compounds. In the present research, the types of glucosinolates, the content of glucosinolates and the activity of myrosinase of the purple variety of fresh raw mashua and in mashua treated by several types of processing were evaluated, including the previous treatment (sunny and unscrewed), the boiling treatment and the microwave treatment, with whitening times of 3, 4, 5 and 6 minutes, being the condition of the tuber at the time of bleaching in whole form and by cutting, to then be subsequently subjected to lyophilization treatments. Five glucosinolatos (GSL) were identified: 5-methylsulfinilpentile, 4-hydroxybenzyl, 4-hydroxy-3-indolylmethyl, benzyl and 4-methoxybenzyl, of which 4-methoxybenzyl glucosinolate is the most abundant, symbolizing 98% and 95% of the total GSL in the purple ecotype. According to the total concentration of glucosinolates found in the studied variety (purple), it must be 74.22 and 110.60 micromoles per gram of dry base (μmol/g dry weight), so mashua can be considered, the edible plant with the highest existing GSL content.